Does Excess Liquidity Pose a Threat in Japan? - Eggertsson, Gauti (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2005)
This paper examines the effects of quantitative easing implemented by the Bank of Japan (BoJ) since early 2001, looking specifically at the impact on inflation expectations and real asset prices. It suggests a number of possible channels through which quantitative easing may have exerted influence, and reviews some of the empirical evidence linking open market operations and long-term bond purchases to real yields and other asset prices. It argues that quantitative easing has had smaller effects on nominal and real variables than desired, mainly because the BoJ has not succeeded in credibly communicating its policy intentions once the zero bound on short-term rates ceases to be binding. It argues that setting clear goals for inflation and a return to interest rate targeting are not only key elements of a successful strategy to avoid deflation, but are also essential to pin down expectations and avoid instability once deflation wanes.